Asas Unus Testis Nullus Testis dalam Tindak Pidana Pemerkosaan Anak - Ni Made Yulia Chitta Dewi; A.A. Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2021)
Proving a criminal act of child rape must have valid evidence. The evidence itself aims to find material truth in order to prove whether the defendant is guilty or not. If in proving a criminal act of child rape, the judge considers that there is only one valid witness testimony and it is not supported by other evidence, of course this will become a consideration for the judge's decision. This study aims to analyze the principle of unus testis nullus testis in the crime of child rape and to find out the evidence of the crime of child rape by using one witness (unus testis nullus testis). The type of research used is normative research and conceptual approaches. The results showed that the testimony of the witnesses in the process of evidence was the main evidence for the judge's consideration. In criminal procedural law, the process of proof is carried out by presenting witnesses and supported by other evidence. In addition to the case of child rape, other than using witness testimony, other supporting evidence is needed, such as the results of a visum et repertum which are useful to prove that a crime has occurred. Independent witness statements must be followed by other valid evidence to strengthen the witness's testimony. To prove a crime of child rape, if there is only one witness, this cannot prove that the crime has occurred